Gender and International Research Cooperation - Vabø, Agnete (International Higher Education, 2012)
This article discusses why U.S. academics, and female academics in particular, are less involved in international collaboration than their colleges in other countries. Features of the U.S. system for higher education and research, including its size, academic quality and the nature of the academic tenure track career system, are important in shaping this "national-oriented" mode of academic work. It is argued, however that such qualities also limit the realization of academic and economic potential of international research collaboration.